Professional preferences and employment prospects of young people with disabilities - E. V. Kuznetsova; V. A. Yudina; A. A. Lushnikov (Вестник университета)
Today, the mainstream in the development of inclusive social initiatives is to create equal conditions for every member of society. The results of sociological studies that determine the main preferences in the field of career building and employment opportunities for young people with disabilities are presented. The main behavioural characteristics of this category of young people are described. The most useful skills acquired in the process of studying in educational institutions were the ability to listen, manage time, conflicts. These are the qualities that any person needs to effectively organise his life, establish contacts, establish interpersonal relationships. The study revealed the desire of young people with disabilities to look for work, find a job, but often the jobs provided by employers do not meet the necessary minimum requirements or the physical abilities of job seekers do not allow them to find a job. This study has made it possible to outline the range of problems faced by young people with disabilities in finding employment and choosing a career.